2013
DOI: 10.2190/de.43.2.e
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Perceptions of Their Roles in Alcohol Education/Prevention

Abstract: Alcohol use among college students continues to be a major public health threat to our nation. The purpose of this study was to explore faculty perceptions of their roles and responsibilities in alcohol education and prevention. The researchers adapted the Core Faculty and Staff Environmental Alcohol and Other Drug Survey to include only questions regarding alcohol and created additional questions concerning Friday classes. The survey was sent to all faculty members (N = 1,712). Completed surveys were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…These relationships, if not actively managed, can easily involve alcohol. However, this is in direct conflict with new administrative efforts and policies to curb student drinking, which many top academic officials now believe is a major public health threat (Johnson, 2013; Walter, Paulo, & Polacek, 2002). Dissonance is stoked when students drink with their professors—the very employees of the university asking students not to drink.…”
Section: Unexamined Assumptions Of Faculty–student Relationshipsmentioning
confidence: 99%
“…These relationships, if not actively managed, can easily involve alcohol. However, this is in direct conflict with new administrative efforts and policies to curb student drinking, which many top academic officials now believe is a major public health threat (Johnson, 2013; Walter, Paulo, & Polacek, 2002). Dissonance is stoked when students drink with their professors—the very employees of the university asking students not to drink.…”
Section: Unexamined Assumptions Of Faculty–student Relationshipsmentioning
confidence: 99%
“…This study demonstrated that the social norms approach can also be effective when employed in a classroom setting. In addition, while research has shown that most faculty members are confident in their ability to positively impact alcohol behavior (Walter et al., 2013), outcomes of curriculum infusion programs are mixed, and methods are often muddled. This creates the potential for confusion and uncertainty when deciding the type of program to infuse into their courses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the efficacy of different forms of CI has not been adequately addressed. With growing faculty interest in classroom-based alcohol interventions (Walter, Paulo, & Polacek, 2013), this study attempts to explore the limitations in previous research to provide guidance for faculty members and health educators looking to effectively address this issue in the classroom.…”
mentioning
confidence: 99%
“…While several studies focusing on the views on roles and responsibilities in relation to substance use prevention have been conducted in a non-European context [8][9][10][11][12][13], less research with this focus has been conducted in Europe and the Nordic countries. Considering the available European research, one Irish study [14] showed that teachers deemed parents as most suited to educate and prevent student alcohol and cannabis use, followed by the students' general practitioner and other health and welfare representatives, while teachers (themselves and other teachers) were viewed as slightly less suited to this task.…”
Section: Introductionmentioning
confidence: 99%